LITERATURE REVIEW: SIARAN LANGSUNG TIKTOK TERHADAP KESADARAN MEREK, KEPERCAYAAN MEREK, DAN KEPUTUSAN PEMBELIAN - Yuningsih, Yuningsih; Lukita, Chandra; Pranata, Sudadi; Lubis, Dokmen; Nolen, Jeammy (Fakultas Ekonomi dan Bisnis, 2024)
This research examines the influence of TikTok live streaming in the context of marketing and consumer behavior. It aims to provide deeper insights into how TikTok live streaming affects consumer behavior, including enhancing brand awareness, strengthening brand trust, and influencing purchase decisions. The method used in this research is qualitative research with a literature review approach. The results of the study indicate the importance of TikTok live streaming in the context of marketing and consumer behavior. Marketing strategies utilizing live streaming need to be tailored to the characteristics of the target market and the desired objectives. Creating brand awareness and generating engaging content on social media can enhance consumer trust and drive purchase decisions.Kata kunci: Interaktivitas, Kepercayaan merek, Keputusan pembelian, Kesadaran merek, Siaran Langsung TikTok